2019
DOI: 10.1093/jac/dkz392
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of repeating a social norm feedback intervention to high prescribers of antibiotics in general practice: a national regression discontinuity design

Abstract: Objectives Unnecessary antibiotic prescribing contributes to antimicrobial resistance. A randomized controlled trial in 2014–15 showed that a letter from England’s Chief Medical Officer (CMO) to high-prescribing GPs, giving feedback about their prescribing relative to the norm, decreased antibiotic prescribing. The CMO sent further feedback letters in succeeding years. We evaluated the effectiveness of the repeated feedback intervention. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(41 citation statements)
references
References 23 publications
(23 reference statements)
1
40
0
Order By: Relevance
“…12 However, while physicians remain hesitant about the approach of tracking and reporting antibiotic use, studies from the USA and UK have shown that this stewardship approach is effective at reducing inappropriate prescribing. [43][44][45][46][47] Additional studies have evaluated physician perceptions of broader quality measurement systems. One study of US physicians in three states found that 71% felt that paediatric quality reports were effective at improving paediatric care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 However, while physicians remain hesitant about the approach of tracking and reporting antibiotic use, studies from the USA and UK have shown that this stewardship approach is effective at reducing inappropriate prescribing. [43][44][45][46][47] Additional studies have evaluated physician perceptions of broader quality measurement systems. One study of US physicians in three states found that 71% felt that paediatric quality reports were effective at improving paediatric care.…”
Section: Discussionmentioning
confidence: 99%
“… 12 However, while physicians remain hesitant about the approach of tracking and reporting antibiotic use, studies from the USA and UK have shown that this stewardship approach is effective at reducing inappropriate prescribing. 43–47 …”
Section: Discussionmentioning
confidence: 99%
“…Prescribing was decreasing in both trial arms over the outcome period from March 2018 to September 2018 (β < −0.01, p < 0.001). The lack of effect of the intervention was surprising, given the evidence of effectiveness of previous social-norms-feedback letters to GPs in the UK (Hallsworth et al 2016;Ratajczak et al 2019) and internationally (Behavioural Economics Team of the Australian Government 2018; HSC Public Health Agency 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Based on this evidence, similar letters were sent out to all practices whose prescribing was in the top 20% nationally in 2015/16 and 2016/ 17 (the NHS Local Area Teams, which were used in the original letter, had been disbanded). An evaluation of the 2016/17 letter using a regression discontinuity design showed that the letter continued to have an effect, causing a 3.69% reduction in prescribing, with an estimated 124,952 fewer antibiotic items dispensed (Ratajczak et al 2019). The intervention has also been successfully implemented in Ireland and Australia (Behavioural Economics Team of the Australian Government 2018; HSC Public Health Agency 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The intervention has supported GPs to reduce their prescribing further by providing feedback on practice prescribing rates, offering encouragement and suggesting practical actions in a clear and succinct manner. 118 Governments may also introduce financial incentives to reduce prescription of antibiotics. For instance, in 2015, NHS England introduced rewards to clinical commissioning groups for a percentage reduction in antibiotic prescribing.…”
Section: Novel Regulatory Interventionsmentioning
confidence: 99%